Referential interpretation of vernacular heritage in recent architectural design - Aslan, Emrah; Ertürk, Doğan Zafer; Ertürk, Sevinç (Scuola Pitagora Editrice, Piazza Santa Maria Degli Angeli, 1, Napoli, 80132, Italy, 2015)
This research is designed to look for the influences of vernacular heritage in contemporary architecture, using different design actions; imitation, bricolage, analogies, interpretation and mimesis. In order to search for the possible effect of vernacular heritage on contemporary architectural practice, seventeen cases have been analyzed with interviewing architects. The data collection method has been chosen carefully and applied in several different ways: literature review, digital documents, observations, sketches and scaled drawings; semi-structured interviews with the designer in order to catch their intentions in case studies. The result of the research showed that the Anatolian vernacular archetypes are being used by the architects in their practices via different level of referential interpretations, design actions. The research goes beyond simple subjective observations of using archetypes; this has been achieved through the development of framework for the systematic classification and analysis of a range of reference types and used both in the interpretation of visual material and in the analysis of documentary sources and interviews with architects. The intentions of each architect have been identified in case studies.
Keywords: Imitation; Bricolage; Analogy; Interpretation; Mimesis